Quantitative indicators of corporatism: A survey and assessment - Lane Kenworthy (Max-Planck-Institut für Gesellschaftsforschung, 2000)
Corporatism has been one of the most heavily studied concepts in comparative political economy over the past two decades, and quantitative indicators of corporatism have played a central role in the corporatist literature. This paper offers a survey and assessment of 42 such indicators. The principal aims are to provide an inventory of existing indicators, to examine their relative trustworthiness and utility, and to assess the robustness of empirical findings on the effects of corporatism on macroeconomic performance and income distribution and redistribution. Among the more noteworthy conclusions I reach are the following: (1) While quantitative corporatism measures have improved substantially in recent years, substantial gaps remain. (2) There is little justification for continued use of time-invariant measures. (3) Composite corporatism measures are commonplace, yet their creators and users have yet to offer a compelling explication of how corporatist effects are generated in such a way that they are more accurately captured by aggregated indicators than by narrowly-targeted ones. (4) There is fairly strong indication that one or more aspects/types of corporatism were associated with nominal wage restraint, low inflation, low unemployment, and low income inequality during the 1970s and 1980s. However, the results vary markedly depending upon the particular indicator used, and there is little evidence to support the common presumption that corporatism's unemployment-reducing effect occurs via real wage restraint. – – Wenige Modelle der vergleichenden politischen Ökonomie sind über die vergangenen 20 Jahre so eingehend untersucht worden wie das des Korporatismus. In der einschlägigen Literatur spielen dabei quantitative Indikatoren eine zentrale Rolle. Für das vorliegende Discussion Paper sind 42 Indikatoren erhoben und untersucht worden. Ziel war es, sie auf ihre Brauchbarkeit und Verläßlichkeit hin zu überprüfen sowie herauszufinden, wie standfest empirische Untersuchungen über die Auswirkungen des Korporatismus auf makro-ökonomische Leistungsfähigkeit, Einkommensverteilung und -umverteilung sind. Zu den besonders erwähnenswerten Schlußfolgerungen dieses Discussion Papers gehören: (1) Trotz immer noch bestehender Mängel haben sich quantitative Koporatismusmaße in den letzten Jahren als stichhaltig erwiesen. (2) Die Anwendung konstanter Variablen ist nicht mehr sinnvoll. (3) Summarische Korporatismusindikatoren werden zwar oft verwendet, doch ihre Erfinder und Anwender bleiben eine einleuchtende Erklärung schuldig, warum korporatistische Effekte besser durch aggregierte Gesamtmaße als durch sachlich genauere Einzelindikatoren erklärt werden sollten. (4) Alles weist darauf hin, daß einige Aspekte oder Formen des Korporatismus mit Lohnzurückhaltung, niedriger Inflation, höherer Beschäftigung und weitgehender Einkommensgleichheit in den 70er und 80er Jahren korrelieren. Die Ergebnisse variieren jedoch stark, je nachdem, welcher Indikator zugrunde gelegt wurde, und wenig stützt die allgemeine Vermutung, daß der Korporatismus vor allem durch Lohnzurückhaltung die Arbeitslosigkeit mindert.
Keywords: 300